Contribución a la historia ambiental de la ciudad de Sogamoso, 1900 – 1950 (2016)
The method of environmental interpretation proposed by Augusto Angel Maya was used In the research. The purpose of this is to make an environmental history of Sogamoso, between 1900 and 1950 period. An emphasis between the ecosystem relations and the cultural system is made. Culture in this method is conceived as a strategy of adaptation in front of eco systemic environment . This is constructed based on the demographic behavior , technological development, social organization and the symbolic world. This period permits to observe the environmental transformations In the research in Sogamoso before the modern industry arrived. The society in Sogamoso was characterized by an agricultural tradition.